Akkermansia muciniphila - friend or foe in colorectal cancer? - Gubernatorova, Ekaterina O.; Gorshkova, Ekaterina A.; Bondareva, Marina A.; Podosokorskaya, Olga A.; Sheynova, Anna D.; Yakovleva, Anastasia S.; Bonch-Osmolovskaya, Elizaveta A.; Nedospasov, Sergei A.; Kruglov, Andrey A.; Drutskaya, Marina S. (Frontiers in Immunology, 2023)
Akkermansia muciniphila is a gram-negative anaerobic bacterium, which represents a part of the commensal human microbiota. Decline in the abundance of A. muciniphila among other microbial species in the gut correlates with severe systemic diseases such as diabetes, obesity, intestinal inflammation and colorectal cancer. Due to its mucin-reducing and immunomodulatory properties, the use of probiotics containing Akkermansia sp. appears as a promising approach to the treatment of metabolic and inflammatory diseases. In particular, a number of studies have focused on the role of A. muciniphila in colorectal cancer. Of note, the results of these studies in mice are contradictory: some reported a protective role of A. muciniphila in colorectal cancer, while others demonstrated that administration of A. muciniphila could aggravate the course of the disease resulting in increased tumor burden. More recent studies suggested the immunomodulatory effect of certain unique surface antigens of A. muciniphila on the intestinal immune system. In this Perspective, we attempt to explain how A. muciniphila contributes to protection against colorectal cancer in some models, while being pathogenic in others. We argue that differences in the experimental protocols of administration of A. muciniphila, as well as viability of bacteria, may significantly affect the results. In addition, we hypothesize that antigens presented by pasteurized bacteria or live A. muciniphila may exert distinct effects on the barrier functions of the gut. Finally, A. muciniphila may reduce the mucin barrier and exerts combined effects with other bacterial species in either promoting or inhibiting cancer development.